Numerical Analysis and Design Provision Development for the Simple for Dead Load–Continuous for Live Load Steel Bridge System - Farimani, Reza; Javidi, Saeed; Kowalski, Darek; Azizinamini, Atorod (Engineering Journal, 2014)
The proposed connections of steel bridge girders at the pier for the simple for dead load and continuous for live load concept (SDCL) were investigated. Analytical models were developed for four connection types that previously were tested in the structural lab. For the numerical modeling of the tested specimens, nonlinear finite element was utilized. The behavior of the numerical models of each tested specimen was verified by the experimental results. The force resistance mechanism of each specimen was studied using the experimental and numerical data. In developing a resistance mechanism for the connections, the yielding of the rebar in the slab, the steel girder bottom plate and the crushing of the concrete diaphragm at pier were considered. A set of detailed equations was developed to formularize the connection behavior at the ultimate capacity under negative flexure. The developed equations show a good agreement with the finite element analysis results. For practical purposes, simplified equations were derived from the more detailed equations to calculate the negative ultimate flexure capacity, at the section through the pier, for two connection types. To verify the proposed design equations for a wider range of bridges, a parametric study was performed. The nonlinear finite element models of the bridges from the parametric study were used for verification of the proposed equations.